A Composição Sociopolítica do Legislativo Brasileiro: uma análise da Comissão de Meio Ambiente e Desenvolvimento Sustentável (2004-2015) - Corrêa, Carolina Pimentel (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2018)
The Legislative power, traditionally studied by Political Science, is an object that can and should also be analyzed by Political Sociology. Using Pierre Bourdieu’s theory, this article aims to observe the sociopolitical composition of the Environment and Sustainable Development Commission of the Brazilian Chamber of Deputies from 2004 to 2015. Based on the analysis of the Annual Reports of the Commission, this paper observes the level of schooling, gender, age group and the professions of the members of parliament. The research also highlights the length of time the parliamentarians spend in the Commission, as well as their allocation into the different parties.